Territorial self-governing units of the Czech Republic as entities possessing ownership and other proprietary rights (the basic conceptual issues) - Petr Havlan; Jan Janeček (DANUBE: Law, Economics and Social Issues Review, 2016)
The property owned by self-governing units represents an important socioeconomic factor with the potential to affect a wide range of aspects of life, considering the scope of self-governing units. The aim of this paper is to present an overview of the recent legal regulations regarding the proprietary position of Czech self-governing units (municipalities and regions) as well as comments on their development (considering wider circumstances) from 1990 to the present day. It focuses on the nature of legal entities sui generis (in Czech called "péríspéevková organizace"), which perform ownership and other proprietary rights of the municipalities and regions on the basis of specific public law relations. Appropriate attention is also dedicated to other legal subjects operating in the sphere of territorial self-government considering their proprietary position. The sub-objectives of the article are the identification and explanation of solutions to the identified problems concerning the analyzed questions. The methodological part of the article is based on the analysis and critical evaluation of the current state of the discussed legal issues. The authors use the methods of legal hermeneutics to obtain correct interpretations of the analyzed legal regulations. The entities sui generis in question are found to be a relic of the transition period in Czech legal development after the 1990s and should be replaced with up-to-date forms of a public legal entity.
Keywords: 330; Czech Republic; Ownership; Property; Proprietary Rights; Public Administration; Self-governing Units